Role and distribution of astaxanthin in spiny lobster, Jasus lalandii - Matumba, Tshifhiwa Given (Department of Biological Sciences, 2014)
The occurance and distribution of astaxanthin in tissues of the spiny lobster, Jasus lalandii was investigated. The concentration of astaxanthin was quantified in the exoskeleton, haemolymph, muscles, gonads and hepatopancreas as well as in egg parcels from berried females during the moult as well as the reproductive cycles. Astaxanthin was the dominant carotenoid in all tissues, but small amounts of other carotenoids were detected. Exoskeleton, ovaries and extrude egg parcels had significantly higher astaxanthin concentration than haemolymp, muscles and hepatopancreas. This distribution of astaxanthin was found in both captive and free-living spiny lobsters. Free-living spiny lobsters generally had higher astaxanthin concentration than the captive spiny lobsters although the data is not statistically significant in all tissues investigated.